Inulin in poultry production - BUCŁAW, M. (World's poultry science journal, 2017)
Since 2006, when the European Union imposed a total ban on the use of antibiotic growth promoters, scientific interest has focused on natural feed additives that might be positive to both production performance and animal health. Inulin is a prebiotic, which occurs naturally in many plants as a storage material. The specific structure of inulin underlies the fact that it is not digested by the host digestive enzymes. Unchanged, the prebiotic reaches the large intestine, where it undergoes fermentation and becomes a substrate for some strains of healthy bacteria. Current literature contains information on the effects of inulin on broiler performance and laying performance of hens. It may be concluded from data available that inulin is beneficial in the production of poultry meat and eggs. Inulin may improve feed intake and conversion, stimulate weight gains, strengthen the skeletal system, improve carcass yields and the production and quality of eggs. However, reports on the subject are scarce, and the results they present vary substantially. The mode of action of inulin appears to be complex, multidirectional and is not yet fully understood. The ambiguous character of inulin may result from the fact that its effectiveness in poultry nutrition depends on a number of factors. Despite these unresolved issues, the positive properties of inulin may be of benefit to the poultry industry.